1993
DOI: 10.1037/0033-2909.113.3.487
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style as context: An integrative model.

Abstract: Work on this article was supported by grants from the Lilly Endowment and the William T. Grant Foundation. Our thanks to Diana Baumrind, Marsha Weinraub, and several anonymous reviewers for their thoughtful comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

121
2,839
19
380

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,505 publications
(3,359 citation statements)
references
References 46 publications
121
2,839
19
380
Order By: Relevance
“…However, in the context of low perceived parental warmth, adolescents may view these same tactics in a less favorable light: i.e., as intrusive, unwarranted, and manipulative. These findings are consistent with Darling and Steinberg's (1993) argument that the overall quality of the parent-child relationship may influence how adolescents respond in domain-specific interactions-in this instance, when parents attempt to influence adolescent's diet. The current results are consistent with the findings of Okun et al (2007), who found that positive social control from a romantic partner was only associated with positive behavior change in the context of a high-quality dating relationship, among college undergraduates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the context of low perceived parental warmth, adolescents may view these same tactics in a less favorable light: i.e., as intrusive, unwarranted, and manipulative. These findings are consistent with Darling and Steinberg's (1993) argument that the overall quality of the parent-child relationship may influence how adolescents respond in domain-specific interactions-in this instance, when parents attempt to influence adolescent's diet. The current results are consistent with the findings of Okun et al (2007), who found that positive social control from a romantic partner was only associated with positive behavior change in the context of a high-quality dating relationship, among college undergraduates.…”
Section: Discussionsupporting
confidence: 88%
“…During adolescence, youth seek increasing autonomy (Silverberg and Steinberg 1987), and social control attempts by parents that are perceived as threats to their emotional or behavioral freedom are not likely to produce positive results (Barber and Harmon 2002). Darling and Steinberg (1993) argued that the emotional climate of the parent-adolescent relationship may influence the effectiveness of parental socialization practices, proposing that the latter are more effective in higher-quality parentadolescent relationships that are characterized, among other things, by warmth and understanding (see also Hoffman 1983). Thus, the effectiveness of parents' attempts to influence their adolescent children's diet may be contingent on parents' ability to convey warmth and acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Although research based on Baumrind's typological approach to parenting has yielded an impressive body of findings linking parenting behavior to child outcome, this approach does not allow us to examine the impact of specific constituents (e.g., warmth) of the constellation on child externalizing behaviors (Darling & Steinberg, 1993;Davidow & Grusec, 2006). In other words, this focus on the composite parenting behavior (e.g., warmth plus firm control in authoritative parenting) and its relation to child outcome impedes the dismantling of the typology, by which it might be determined that an individual parenting behavior (e.g., warmth) is primarily associated with a specific child outcome (e.g., decreased levels of child externalizing symptoms).…”
Section: Broad Typologies Of Parentingmentioning
confidence: 99%
“…In contrast to parenting practices focused on directly influencing what a child eats (e.g. restriction of food, serving fruits and vegetables, pressure to eat), general parenting refers to the 'style' that parents adopt in their interactions with their children (14) . Parents can fall into one of four general parenting 'styles' based on two dimensions: demandingness (i.e.…”
mentioning
confidence: 99%